Assessment of cyclists' pedaling techniques by patterns of muscle bioelectrical activity - Lukashevich, D. A.; Vasyuk, V. E.; Zyryanov, K. V.; Shipovskaya, V. V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the features of the parameters of bioelectric activity of muscles that characterize the pedaling technique using the electromyography method.